2021
DOI: 10.2147/dmso.s342185
|View full text |Cite
|
Sign up to set email alerts
|

Affective Temperament and Glycemic Control – The Psychological Aspect of Obesity and Diabetes Mellitus

Abstract: Purpose Affective temperament shows innate predisposition to affective disorders and has been studied in patients with type 2 diabetes mellitus (T2DM) and obesity. Studies describing connections between depressive disorders, obesity and T2DM, show a bidirectional way in which these disorders affect each other. Given that obesity, depression, and T2DM are still growing health problems of our times, the improvement of therapeutic strategies is required. The aim of our study was to evaluate affective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 72 publications
(64 reference statements)
0
11
0
Order By: Relevance
“…Though void of any pathological value per se, affective temperaments may nonetheless represent vulnerability factors towards the development of various configurations of mood [ 4 ] as well as other psychiatric disorders [ 5 ] and specific somatic conditions [ 6 17 ]. Affective temperaments may also affect the long-term course and treatment outcome of various conditions, although evidence modeling the relationship between affective temperaments and the prognosis of somatic diseases is tentative [ 13 , 15 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Though void of any pathological value per se, affective temperaments may nonetheless represent vulnerability factors towards the development of various configurations of mood [ 4 ] as well as other psychiatric disorders [ 5 ] and specific somatic conditions [ 6 17 ]. Affective temperaments may also affect the long-term course and treatment outcome of various conditions, although evidence modeling the relationship between affective temperaments and the prognosis of somatic diseases is tentative [ 13 , 15 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the relationship between psychology and infertility, different models have evolved since the 1940s [39], starting with the since outdated psychogenetic model, which considered psychopathology and unconscious psychological processes as the sole causes of biologically unexplained infertility [40], followed by various psychosomatic models, which likewise focus on the psychological contributors of the development of infertility [39], the most intensively researched of which is the stress hypothesis, which examines the association between neuroendocrine sequalae of chronic stress and fertility problems [41]. Stress was found to be associated with uctuations in blood sugar levels, insulin resistance, obesity, hypothyroidism or hyperprolactinemia, all of which may complicate achieving pregnancy [42,43], and some of which somatic conditions have already been associated with affective temperaments [25,26,34,[44][45][46]. More recent results also suggest that the effects of stress may not be mediated by the abovementioned hormonal-biological factors, but instead operate through deterioration of health behaviours, some of which are also associated with affective temperaments [47,48], such as smoking, alcohol intake, drug use and lack of physical activity [24].…”
Section: Discussionmentioning
confidence: 99%
“…But what is even more important from clinical perspective, is that among women with infertility problems, affective temperament pro le robustly in uences the chance of getting pregnant, which implies that our results may have direct clinical consequences regarding fertility treatment. Although affective temperaments are relatively stable during the lifespan, they in uence several modi able risk factors of infertility, such as depression and anxiety [7], weight, nutrition, exercise, smoking and other self-harm behaviours [25,27], or adherence to the treatment protocol, medication, and lifestyle changes advised by the doctor [51]. Further studies are needed to understand what mediates this affective temperament-infertility treatment outcome relationship for different temperament pro les, considering psychological pathways and processes such as emotional stability and reactivity, cognitions, and behaviours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Affective temperaments (depressive, cyclothymic, hyperthymic, irritable, and anxious) represent vulnerability factors towards the development of various psychiatric 17,18 and somatic diseases [19][20][21][22][23][24][25][26][27][28][29][30] and affect the long-term course and treatment outcome of several of these conditions 17,26,28,31 . In a previous study, we reported that affective temperaments also affect infertility treatment success 32 , and we discussed that the necessary next step is to identify the processes and factors through which they exert their in uence, and which may be modi able with psychological interventions and patient-centered, targeted therapy.…”
Section: Introductionmentioning
confidence: 99%